MENGURANGI HIPERAKTIFITAS PADA ANAK ATTENTION DEFICIT/HIPERACTIVITY DISORDER (ADHD) MELALUI PERMAINAN TRADISIONAL TEROPA TEMPURUNG (Single Subject Research Kelas III Di SLB Negeri Lima Kaum) - Meliastari - Meliastari (Jurnal Penelitian Pendidikan Khusus, 2012)
This study aimed to determine whether the traditional game terompa shell to reduce hyperactivity in children attention deficit / hyperactivity disorder (adhd). This research was conducted at The Lima Public SLB Tanah Datar. Type of research is experimental research that is used in the form of SSR (Single Subject Research). Experimental study is an experiment that is used to examine an event or symptoms of a certain situation be it positive or negative. The design of this study AB, according Sunanto Juang (2005:57), AB design procedure developed on the basis of logic baseline, baseline logic shows a measurement repeatability of behavior on at least two conditions, namely: baseline condition (A) and intervention condition (B) . The results of this study indicate the initial condition (A) kehiperaktifitasan on the behavior of children with ADHD can not sit still for six days in his chair fixed data, the same child can not sit still in his chair (100%). It can be seen from the observation of the children for six days. While in the intervention condition (B) after using the game as a means of reducing the shell terompa child hyperactivity in behavior can not sit still in his chair seen to decrease. This is done for nine meetings. Nine of the meeting, hyperactivity children can be reduced by 78% so that the behavior of the child can not sit still in his chair to 22%. This shows that the traditional game terompa shell can reduce ADHD child kehipraktifitasan.